1990
DOI: 10.1042/bj2710351
|View full text |Cite
|
Sign up to set email alerts
|

A pH-dependent activation-inactivation equilibrium in glutamate dehydrogenase of Clostridium symbiosum

Abstract: 1. On transferring Clostridium symbiosum glutamate dehydrogenase from pH 7 to assay mixtures at pH 8.8, reaction time courses showed a marked deceleration that was not attributable to the approach to equilibrium of the catalysed reaction. The rate became approximately constant after declining to 4-5% of the initial value. Enzyme, stored at pH 8.8 and assayed in the same mixture, gave an accelerating time course with the same final linear rate. The enzyme appears to be reversibly converted from a high-activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…First of all, at neutral pH, whilst the dependence on glutamate concentration appears to follow the conventional Michaelis–Menten pattern, the behaviour with NAD + is complex and shows a pattern of apparent negative cooperativity [12] rather reminiscent of that described many years ago for both NAD + and NADP + with the bovine enzyme [3,5]. On the other hand, at pH 8.8–9.0, a pattern initially described as a pH‐dependent inactivation [13], was later shown to be an aspect of an allosteric conformational equilibrium [14] that could be reversed (reactivation) by glutamate with a remarkable degree of positive cooperativity reflected in a Hill coefficient very close to the theoretical maximum of 6 for a hexamer [15]. For purely historical reasons, the behaviour with variation of coenzyme concentration has not previously been examined in detail at high pH.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…First of all, at neutral pH, whilst the dependence on glutamate concentration appears to follow the conventional Michaelis–Menten pattern, the behaviour with NAD + is complex and shows a pattern of apparent negative cooperativity [12] rather reminiscent of that described many years ago for both NAD + and NADP + with the bovine enzyme [3,5]. On the other hand, at pH 8.8–9.0, a pattern initially described as a pH‐dependent inactivation [13], was later shown to be an aspect of an allosteric conformational equilibrium [14] that could be reversed (reactivation) by glutamate with a remarkable degree of positive cooperativity reflected in a Hill coefficient very close to the theoretical maximum of 6 for a hexamer [15]. For purely historical reasons, the behaviour with variation of coenzyme concentration has not previously been examined in detail at high pH.…”
Section: Introductionmentioning
confidence: 86%
“…[16,17]), but this does not unambiguously indicate whether the two effects rely on separate structural machinery. Recently, however, pursuit of Trp residues thought to be sensing the pH/glutamate-dependent conformational change [14], has highlighted two, W64 and W449, which appear to provide six pairwise interactions across the trimer-trimer interface [18]. Replacement of either of these Trp residues with Phe results in an enzyme that still undergoes ÔinactivationÕ at high pH, but now the response to glutamate shows a greatly diminished Hill coefficient of about 2 [18].…”
Section: Introductionmentioning
confidence: 99%
“…This does not mean however, that, as recently stated [8], allosteric interaction is confined to the GDHs of higher organisms. It has been known for some time that clostridial GDH is indeed still subject to homotropic allosteric regulation [9–11]. At neutral pH, the rate dependence on NAD + concentration shows a pattern of negative cooperativity [9] that is strikingly similar to that seen with the bovine enzyme [12].…”
mentioning
confidence: 99%
“…The hexameric clostridial GDH, like some from other sources [13], also undergoes pH‐dependent loss of activity [10] attributed to conformational change [14]. A later study [11], however, showed that the apparent inactivation could be reversed merely by increasing the glutamate concentration.…”
mentioning
confidence: 99%
“…This account is applicable to other members of the GDH family [7] in view of the high degree of conservation of key structural features. There are, however, unanswered questions with regard to the hnctional properties specific to clostridial GDH, notably in terms of its behaviour at alkaline pH, where it undergoes timedependent, inactivating conformational change [8] and where the measurable activity does not show [9] the shift in specificity towards monocarboxylic acid substrates seen, for example, in bovine GDH [lo] The search for a structural basis for these hnctional differences has directed attention to Asp 114. This is adjacent in the primary sequence [ 1 I , 121 to Lys 1 13, one of the three essential lysine residues identified by chemical modification [U], now shown to be involved in recognition of the a-COO-of the substrate glutamate [ 2 1 In all other reported GDH sequences this position is occupied by a neutral residue, usually asparagine or cysteine.…”
mentioning
confidence: 99%